THE ANALYSIS OF COMMUNICATION ACCOMMODATION STRATEGIES USED BY STUDENTS OF ENGLISH LANGUAGE EDUCATION OF GANESHA UNIVERISTY OF EDUCATION - Suputra, D. P. R.; Ramendra, D. P.; Swandana, I. W. (Universitas Pendidikan Ganesha, 2020)
Language development affects human speech. Speech is the way of communication. The purpose of communication involves how the information can be transferred to each other. People accommodate their communication in daily life to achieve the goal of communication. Another possible purpose which is expected by communicator is showing an identity. It can be done by using strategy based on Communication Accommodation Theory. Communication accommodation strategy is divided by two, divergence and convergence strategy. Phenomena of the use of convergence and divergence exist on students of English Language Education of Ganesha Univerisity of Education. English Language Education students are prepared as a teacher who needs prior knowledge about communication strategy that is expected for communication skill development. The population of the study is students of English Language Education of Ganesha University of Education who are from each regencies in Bali. This study used qualitative method with descriptive design which is expected can describe the use of Convergence and Divergence strategy within the reason of using each strategy. The variables being analyzed are speech rate, pauses, utterance length and lexical accommodation. The data is collected through observation and interview session. The result of study shows that students are possible to use multiple strategy in each variable based on current circumstance. The circumstance involves the place, interlocutor, intimacy, and speech community. All students uses convergence strategy in all variable and three of them use divergence strategy lexically. The reason of using each communication accommodation strategy is taken from communication accommodation theory.Keywords: Communication Strategy, Communication Accommodation Theory